2002
DOI: 10.1067/mob.2002.126848
|View full text |Cite
|
Sign up to set email alerts
|

The postpartum visit: Risk factors for nonuse and association with breast-feeding

Abstract: Objective-Our purpose was (1) to describe use of the postpartum visit among US women of different social and ethnic backgrounds and to identify risk factors for nonuse and (2) to determine the association between postpartum care and breast-feeding duration.Study Design-The responses of a nationally representative sample of 9953 women who had a live birth in 1988 surveyed by the National Maternal and Infant Health Survey were included for our secondary analysis. Risk factors for nonuse of the postpartum visit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…Additionally, there was significant racial, ethnic, and socioeconomic diversity reflected in our study population. Prior studies have shown that women who are financially and socially disadvantaged may be less likely to attend postpartum visits 4 , and certainly this may have contributed to some loss to follow-up among women in this study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, there was significant racial, ethnic, and socioeconomic diversity reflected in our study population. Prior studies have shown that women who are financially and socially disadvantaged may be less likely to attend postpartum visits 4 , and certainly this may have contributed to some loss to follow-up among women in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Women who intend to use an intrauterine device (IUD) for postpartum contraception are often unable to return for a postpartum visit, and never receive anIUD. 3 These women are more likely to be socially and financially disadvantaged 4,5 and face barriers such as lack of transportation, lack of stable housing, and difficulty communicating with their healthcare providers. 6 …”
Section: Introductionmentioning
confidence: 99%
“…8 Our findings of 14% of mothers with vaginal births and 11% of mothers with cesarean births having no clinic visits during the 2 months after discharge (excluding visits in the first week after discharge) add to the meager knowledge of postpartum visit utilization.…”
Section: Discussionmentioning
confidence: 98%
“…During this period postpartum visits (PPVs) have been advocated as a way to improve outcomes for mothers and their infants. It is believed to offer an important opportunity to assess the physical and psychosocial well-being of them [2]–[5]. However, postpartum care continues to be the “least emphasized” element in maternity services [6], [7], although it is vital for the reduction of diseases and deaths amongst mothers and neonates [8].…”
Section: Introductionmentioning
confidence: 99%